(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The plight of the blighted planet is the greatest tragedy woven by man, but he is horrified by its impact. He made a hell of this heaven. Nothing even science and technology could save him. The pandemic called COVID is an eye-opener. The genetic variant of a minute virus could frighten even the mightiest of empires. The world stands still here. No doubt it is a tragedy created by man. We are reaping the harvest of our own evil deeds. ‗The half-naked fakir‘ is called Mahatma Gandhi and his words reverberate in the Indian firmament like that of a prophet. ―My life is my message‖, he uttered proving his life as an experiment with truth. He believed in reforming himself like Henry David Thoreau. The ideal of Sarvodaya sprang up from his deep thought. It is an attitude that aims at the welfare of all. John Ruskin and his work Unto This Last inspired him and he practiced the ideas in it. Fasting was used as a means to purify the mind. It turned out to be even a weapon to fight injustice. Observation of silence (Mauna Vrat) was also used by him to strengthen himself. His love towards villages arose out of his consideration towards the poor rustics. Even though he didn‘t utter the word ‗ecology‘, he was an advocate of it in essence. Over-dependence on machines, he feared would drain human feelings. The present predicament is the result of the over-exploitation of nature and reckless life. Vegetarianism is also promoted by Gandhi. Man must lead a life sanctified by a deep concern towards others including the environment which is a spiritual way of life also. An attitude immersed in human love and consideration towards nature can usher in peace and prosperity.